Clostridium perfringens in the Environment - Matches, Jack R. (1974)
Clostridium perfringens was isolated from samples collected in Puget Sound in the state of Washington and areas considered as possible sources of these organisms to Puget Sound. The distribution of C. perfringens in the total Clostridium population was determined for fish gut contents and sediments collected in highly polluted and less polluted areas, sewage samples, freshwater sediments, and soils. The greatest numbers of C. perfringens were obtained from marine sediments collected near the sewage outfall at West Point. Fewer isolates were made from fish collected from less polluted stations, although the number of C. perfringens remained high in sediments from other Puget Sound stations. The proportion of C. perfringens in the total Clostridium populations varied between 56 and 71% for sewage samples and only 0.4 to 4.1% for freshwater sediments and soil samples. Only 25 C. perfringens isolates out of 137 from fish guts, or 18%, were identifiable serologically and these fell into 12 groups. C. perfringens were fed to fish and the fish were sacrificed after varying lengths of time. The number of C. perfringens increased slightly in the gut during the first 24 h and then the numbers decreased rapidly for the next 120 h.